1 Transport modes and subjective general health: roles of mental health, social contacts, and physical activity. (18th March 2018) - Avila-Palencia, Ione; Gaupp-Berghausen, Mailin; Raser, Elisabeth; Gerike, Regine; Götschi, Thomas; Kahlmeier, Sonja; Laeremans, Michelle; Dons, Evi; Standaert, Arnout; Panis, Luc Int; Anaya-Boig, Esther; Orjuela, Juan-Pablo; et al.
Abstract : Background/aim: Transport behaviours have been associated with several positive and negative health effects. The current study evaluates the association between different modes of transport and subjective general health in an adult population in seven European cities, and explores whether mental health, vitality, perceived stress, social contacts, and physical activity are mediators of this association. Methods: A longitudinal study was performed in seven European cities (Antwerp, Barcelona, London, Örebro, Rome, Vienna, and Zürich). Participants responded to two comprehensive questionnaires (Baseline and Final) concerning their transport behaviour and health, using an on-line platform. The transport mode usage was assessed using a frequency scale (days/month) of five different transport modes: car, motorbike, public transport, e-bike, bicycle, and walking. Participants were categorised as with 'good or more' or 'less than good' subjective general health. Multilevel regression models will be used to evaluate the association between transport mode and subjective general health, adjusting for potential confounders. We will follow Vander Weele's framework to establish the mediation roles. Results: (ongoing analyses): The sample had more than 7000 adults, fairly distributed in the seven cities (16% Antwerp, 16% Barcelona, 14% London, 10% Örebro, 14% Rome, 16% Vienna, 14% Zürich). In initial analyses we find positive associations between active transport modes (e-bike, bicycle, walking) and subjective general health and negative associations between motorised transport modes (car, motorbike, public transport) and subjective general health. We also expect to find indications for mediation of these associations by mental health, vitality, perceived stress, social contacts, and physical activity. Conclusion: We hypothesise that mental health, social contacts, perceived stress, and levels of physical activity may be important consequences of transport behaviours which could lead to different levels of subjective general health.